The success of the Cystic Fibrosis Registry of Turkey for improvement of patient care - Asfuroglu, Pelin; Eyuboglu, Tugba Sismanlar; Aslan, Ayse Tana; Gursoy, Tugba Ramasli; Emiralioglu, Nagehan; Yalcin, Ebru; Dogru, Deniz (Wiley, 2022)
Background Cystic fibrosis (CF) registries play an essential role in improving disease outcomes of people with CF. This study aimed to evaluate the association of newly established CF registry system in Turkey on follow-up, clinical, growth, treatment, and complications of people with this disease. Methods Age at diagnosis, current age, sex, z-scores of weight, height and body mass index (BMI), neonatal screening results, pulmonary function tests, history of meconium ileus, medications, presence of microorganisms, and follow-up were evaluated and compared to data of people with CF represented in both 2017 and 2019 registry data. Results There were 1170 people with CF in 2017 and 1637 in 2019 CF registry. Eight hundred and fourteen people were registered in both 2017 and 2019 of whom z-scores of heights and BMI were significantly higher in 2019 (p = 0.002, p =0.039, respectively). Inhaled hypertonic saline, bronchodilator, and azithromycin usages were significantly higher in 2019 (p =0.001, p = 0.001, p = 0.003, respectively). The percent predicted of forced expiratory volume in 1 sec and forced vital capacity were similar in 2017 and 2019 (88% and 89.5%, p = 0.248 and 84.5% and 87%, p =0.332, respectively). Liver diseases and osteoporosis were significantly higher, and pseudo-Bartter syndrome (PBS) was significantly lower in 2019 (p = 0.011, p = 0.001, p = 0.001, respectively). Conclusions The z-scores of height and BMI were higher, the use of medications that protect and improve lung functions was higher and incidence of PBS was lower in 2019. It was predicted that registry system increased the care of people with CF regarding their follow-up. The widespread use of national CF registry system across the country may be beneficial for the follow-up of people with CF.
Keywords: child; cystic fibrosis; registry